Can television reduce xenophobia? The case of East Germany - Lars Hornuf; Marc Oliver Rieger; Sven A. Hartmann (Kyklos, 2023)
Can television have a mitigating effect on xenophobia? To explore this question, we investigate a natural experiment in which individuals in some regions of East Germany could not—due to their geographic location—consume West German television until 1989. By analyzing survey data from the periods before and after German reunification, we provide evidence that individuals who received West German television during the GDR period and were thus more frequently exposed to foreign media have developed less xenophobia. We document that West German television programs positively affected individuals' attitudes towards foreigners and led to a higher likelihood of supporting refugees, for example by donating money to refugee aid. In addition to the survey evidence, we show that regions that could receive West German television before reunification were less likely to vote for extreme right-wing parties during the national elections from 1990 to 2017, and experienced fewer criminal offenses against refugees.
Keywords: 300